Direct purification of pectinase from Mango (Mangifera Indica Cv. Chokanan) peel using a PEG/Salt-based aqueous two phase system - Mehrnoush, Amid; Sarker, Md. Zaidul Islam; Mustafa, Shuhaimi; Mohd Yazid, Abdul Manap (Molecular Diversity Preservation International (MDPI), 2011)
An Aqueous Two-Phase System (ATPS) was employed for the first time for the separation and purification of pectinase from mango (Mangifera Indica Cv. Chokanan)peel. The effects of different parameters such as molecular weight of the polymer (polyethylene glycol, 2,000–10,000), potassium phosphate composition (12–20%, w/w),system pH (6–9), and addition of different concentrations of neutral salts (0–8%, w/w) on partition behavior of pectinase were investigated. The partition coefficient of the enzyme was decreased by increasing the PEG molecular weight. Additionally, the phase composition showed a significant effect on purification factor and yield of the enzyme. Optimum conditions for purification of pectinase from mango peel were achieved in a 14% PEG 4000-14% potassium phosphate system using 3% (w/w) NaCl addition at pH 7.0. Based on this system, the purification factor of pectinase was increased to 13.2 with a high yield of (97.6%). Thus, this study proves that ATPS can be an inexpensive and effective method for partitioning of pectinase from mango peel.